Anti-FcαRI Monoclonal Antibodies Resolve IgA Autoantibody-Mediated Disease - Bos, Amelie; Aleyd, Esil; van der Steen, Lydia P. E.; Winter, P. J.; Heemskerk, Niels; Pouw, Stephan M.; Boon, Louis; Musters, Rene J. P.; Bakema, Jantine E.; Sitaru, Cassian; Cogné, Michel; van Egmond, Marjolein (Frontiers in Immunology, 2022)
Immunoglobulin A (IgA) is generally considered as a non-inflammatory regulator of mucosal immunity, and its importance in diversifying the gut microbiota is increasingly appreciated. IgA autoantibodies have been found in several autoimmune or chronic inflammatory diseases, but their role in pathophysiology is ill-understood. IgA can interact with the Fc receptor FcαRI on immune cells. We now established a novel IgA autoimmune blistering model, which closely resembles the human disease linear IgA bullous disease (LABD) by using genetically modified mice that produce human IgA and express human FcαRI. Intravital microscopy demonstrated that presence of IgA anti-collagen XVII, - the auto-antigen in LABD- , resulted in neutrophil activation and extravasation from blood vessels into skin tissue. Continued exposure to anti-collagen XVII IgA led to massive neutrophil accumulation, severe tissue damage and blister formation. Importantly, treatment with anti-FcαRI monoclonal antibodies not only prevented disease, but was also able to resolve existing inflammation and tissue damage. Collectively, our data reveal a novel role of neutrophil FcαRI in IgA autoantibody-mediated disease and identify FcαRI as promising new therapeutic target to resolve chronic inflammation and tissue damage.